The effects of dynamic and static stretching methods on speed, agility and power - Bishop, D. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Warm-ups are integral to coaches` and athletes` preparations, yet current research and practice provides conflicting advice on the most effective warm-up procedure for aiding performance. The value of a warm-up is not in question but the role of static stretching within the warm-up is contentious. A number of studies have suggested that static stretching is detrimental to performance (Shrier, 2004), though these have not always employed stretching protocols that reflect those actually used by performers. Many athletes continue to include static stretching as part of their routine, often following a dynamic warm-up. The purpose of the study was to investigate, using realistic protocols, the effects on speed, agility and power of additional static stretching following a dynamic warm-up.